Movimiento propulsado por reacciones químicas y mediante luz en partículas Janus y coloides activos - Requejo, Katherinne I. (2024)
Unlike inert matter in equilibrium, active matter such as biological organisms are out of equilibrium generating motion and assemblies from molecular interactions and chemical reactions in the nano and micro-scale. In the past, such properties were considered to be exclusive of living systems, however, developments in colloidal science have enabled to produce synthetic analogues known as active colloids capable of emulating these properties. In this article, we first introduce active colloids and Janus particles, the most well studied examples of this scientific field. Then, we briefly present the common methods to synthesize these particles and the description of the mechanism of propulsion at the single colloid level. Besides, we describe how these particles generate collective behavior and assemblies in conditions out of equilibrium. Finally, we describe important characteristics of these active colloids for their application in areas such as biomedicine and environmental remediation.